Karma Yoga: A traditional perspective - Rajeshwar Mukherjee (Wolters Kluwer Medknow Publications, 2016)
Background: Karma Yoga is a valid way to the ultimate realization of the Self. It has been emphasized by Yogeśvara Kṛṣṇa in Śrīmadbhagavadgītā. There is a prevalent misconception that the traditional exponents of Advaita Vedānta have declined to accept it as a path leading to supreme illumination. A careful and in-depth study of the traditional works of Śaṅkara and the modern interpretation by Swami Vivekananda reveal that Karma Yoga is not only a very effective path of yoga but it is a pre-requisite to the highest realization. Aim: This paper attempts to unravel the finer shades of Karma Yoga in the light of Vedānta. Method: The real import of yoga is derived from the etymology of the word 'yoga' and from the definition furnished by Patañjali in his Yogasūtra. Then, Karma Yoga has been substantiated as an independent path to the supreme realization through an analytical study. Ideas about the concept have been carefully culled from Śrīmadbhagavadgita and from the works of Swami Vivekananda. The entire discussion has been carried out without compromising Advaita i.e. non-duality, at any point. Results: The study reveals the following results (a) Karma Yoga can lead to the highest realization. (b) It is complementary to Jñāna Yoga and is not opposed to the findings of Advaita Vedānta. Conclusion: Karma Yoga performed in the spirit of discrimination or devotion consummates in the supreme vision of the non-dual reality.